THE DIFFERENCE BETWEEN THE EFFECTS OF CONTINUOUS RUNNING AND INTERVAL RUNNING TRAINING METHODS ON MAXIMUM OXYGEN VOLUME (O2) OF FOOTBALL ATHLETES AT EDUCATION CENTERS AND STUDENT TRAINING (PPLP) ACEH PROVINCE - Hadi, Amirul (Buletin Farmatera, 2019)
The increase in aerobic exercise is influenced by cardiovascular performance, so to improve aerobic exercise it is necessary to increase the VO2 Max value. The purpose of this study is to prove the differences in the effect of continuous running and interval running exercises on VO2 Max in soccer athletes in PPLP Aceh Province. This study used analytic experimental with pre-test and post-test design. The study was conducted at the Harapan Bangsa Stadium in Banda City with a sample of 52 soccer athletes. Data analysis using Independent Sample T-Test. The result is there was an overall difference between continuous running practice and interval running for VO2 max PPLP soccer athletes in Aceh Province. The average VO2 max with the continuous running method exercise is 61.9 better than the running interval is 54.9. Sig value (2-tailed) VO2 max data is 0.001 This means that there was a difference between continuous running and interval running exercises. From these results, it can be concluded that to improve the VO2 max of a professional soccer athlete, training with the continuous running method is recommended compared to the interval running training method.Keywords: Continuous running, Interval running, and VO2 Max